2020
DOI: 10.1177/1535370220977176
|View full text |Cite
|
Sign up to set email alerts
|

Integrating photoacoustic microscopy with other imaging technologies for multimodal imaging

Abstract: As a hybrid optical microscopic imaging technology, photoacoustic microscopy images the optical absorption contrasts and takes advantage of low acoustic scattering of biological tissues to achieve high-resolution anatomical and functional imaging. When combined with other imaging modalities, photoacoustic microscopy-based multimodal technologies can provide complementary contrast mechanisms to reveal complementary information of biological tissues. To achieve intrinsically and precisely registered images in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Aiming at the delivery of complementary contrast in biological tissues, several studies have demonstrated the development of multimodal instruments, effectively combining time-domain (TD) PA microscopy with well-established optical diagnostic techniques such as confocal fluorescence microscopy, multiphoton imaging and optical coherence tomography (OCT) [34]. It is worth mentioning that these hybrid imaging developments have found various significant applications, including the sensitive detection of capillary blood vessels in mice [35][36][37][38], the delineation of ocular anatomy [39][40][41], the investigation of zebrafish larvae [42,43], the measurement of melanin content in fish scales [44] as well as the spatial mapping of pigments in vegetative tissues [45].…”
Section: Discussionmentioning
confidence: 99%
“…Aiming at the delivery of complementary contrast in biological tissues, several studies have demonstrated the development of multimodal instruments, effectively combining time-domain (TD) PA microscopy with well-established optical diagnostic techniques such as confocal fluorescence microscopy, multiphoton imaging and optical coherence tomography (OCT) [34]. It is worth mentioning that these hybrid imaging developments have found various significant applications, including the sensitive detection of capillary blood vessels in mice [35][36][37][38], the delineation of ocular anatomy [39][40][41], the investigation of zebrafish larvae [42,43], the measurement of melanin content in fish scales [44] as well as the spatial mapping of pigments in vegetative tissues [45].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies to develop a deep learning–based method for fully automatic segmentation and registration are needed, for example, between OA/MRI or OA/CT brain imaging data and for position-dependent light fluence correction hold great promise ( Sarah et al, 2019 ; Waterhouse et al, 2019 ; Ni et al, 2020a ; Dean-Ben et al, 2020 ; Hu et al, 2021 ). Additionally, bimodal animal holder ( Gehrung et al, 2020 ; Zhang et al, 2021b ) or concurrent imaging acquisition OA tomography–MRI, OA–fluorescence confocal microscopy, and OA tomography–fluorescence imaging have already been developed ( Chen et al, 2017 ; Zhang et al, 2018b ; Liu et al, 2019b ; Ren et al, 2021 ; Zhang et al, 2021c ; Dadkhah and Jiao, 2021 ; Deán-Ben et al, 2021 ). Further development in synchronized OA-MR platforms for small-animal brain imaging for simultaneous detection will further improve the workflow ( Ren et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Photoacoustic imaging (PAI) has shown great potential in providing detailed views of human anatomy [1][2][3][4][5]. Photoacoustic imaging technology enables high-resolution imaging of human tissues by delivering pulsed laser beams.…”
Section: Introductionmentioning
confidence: 99%